Symbolic Modeling Techniques to Increase Student Academic Resilience During Online Learning - Durrotunnisa Durrotunnisa; Erniati Erniati (Universitas Pendidikan Ganesha, 2023)
The research objective was to apply group counseling and symbolic modeling technique to improve students' academic resilience during online learning at SMP Negeri 15 Palu. This action research used Kemmis and McTaggart's model was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The research participants were eight students who got the lowest academic resilience questionnaire scores on online learning. Data collection techniques were questionnaires, observation instructions, interviews, and documentation.The research results indicated that the average level of student academic resilience during online learning is pre-action by 48.86%, increasing to 65.90% after the first cycle is carried out, and the second cycle increased to 79.54%. The success rate of cycle II has been improved based on the results of reflections from the first cycle. Therefore, it can be concluded that group counseling with symbolic modeling technique can affect increasing students' academic resilience during online learning at SMP Negeri 15 Palu.